Strategic collaboration between UiTM Green Centre and RVMPLUS Sdn. Bhd. to advance campus sustainability - UiTM, UGC (UiTM Green Centre, 2025)
On 27 May 2025, a meeting between the UiTM Green Centre, UiTM Shah Alam and RVMPLUS Sdn. Bhd. was held at the development department's complex meeting room. This collaboration is expected to enhance sustainability efforts and visibility across the UiTM campus.